Indigenous Populations, Plantations, and Agrarian Conflicts in Rural North Maluku during the Colonial Period from the 17th to the 20th Century - Rahman, A. (Diponegoro University, 2024)
North Maluku's history is marked by conflicts between the indigenous people and colonial rulers, spanning from the 17th century to the early 20th century. These conflicts were primarily driven by the seizure of agricultural lands and plantations, especially for clove and nutmeg spices, as well as forest areas and their products in rural areas. The colonial rulers' monopolistic practices, often enforced through contracts or agreements of cooperation and friendship, primarily benefited the colonial government and private sector. This situation led to growing unrest, anxiety, and pressure among the indigenous population, impacting them socially, economically, and politically. Various forms of indigenous resistance emerged, including rebellions and wars. This article explores several key questions: How did agrarian conflicts on indigenous plantation lands in rural North Maluku arise? What was the involvement of indigenous and colonial authorities in these conflicts? What were the impacts and processes for resolving these conflicts? The research findings indicate that agrarian conflicts arose due to several factors. First, the colonial rulers' monopolistic practices, enforced through contracts and cooperation agreements, only benefited the colonial side. Second, the indigenous people's lives were increasingly burdened by colonial social, economic, political, and military policies. Third, colonial rulers deliberately provoked disruptions in the relationships between local kings, native rulers, and their people. This article is based on source studies and field research from the colonial period, utilizing historical research methods: heuristics, criticism, interpretation, and historiography. The colonial and imperialist spirit, with its liberal capitalist views, significantly restricted indigenous freedoms to cultivate spices on their own plantations and manage forest products like resin. Additionally, indigenous people were prohibited from conducting trade with other traders, including fellow natives, traders from other parts of the archipelago, and foreign traders other than the Dutch.